Metastatic Basal Cell Carcinoma: A Biological Continuum of Basal Cell Carcinoma? - Karaninder S. Mehta; Vikram K. Mahajan; Pushpinder S. Chauhan; Anju Lath Sharma; Vikas Sharma; C. Abhinav; Gayatri Khatri; Neel Prabha; Saurabh Sharma; Muninder Negi (Hindawi Limited, 2012)
Basal cell carcinoma (BCC) accounts for 80% of all nonmelanoma skin cancers. Its metastasis is extremely rare, ranging between 0.0028 and 0.55 of all BCC cases. The usual metastasis to lymph nodes, lungs, bones, or skin is from the primary tumor situated in the head and neck region in nearly 85% cases. A 69-year-old male developed progressively increasing multiple, fleshy, indurated, and at places pigmented noduloulcerative plaques over back, chest, and left axillary area 4 years after wide surgical excision of a pathologically diagnosed basal cell carcinoma. The recurrence was diagnosed as infiltrative BCC and found metastasizing to skin, soft tissue and muscles, and pretracheal and axillary lymph nodes. Three cycles of chemotherapy comprising intravenous cisplatin (50 mg) and 5-florouracil (5-FU, 750 mg) on 2 consecutive days and repeated at every 21 days were effective. As it remains unclear whether metastatic BCC is itself a separate subset of basal cell carcinoma, we feel that early BCC localized at any site perhaps constitutes a biological continuum that may ultimately manifest with metastasis in some individuals and should be evaluated as such. Long-standing BCC is itself potentially at risk of recurrence/dissemination; it is imperative to diagnose and appropriately treat all BCC lesions at the earliest.